Annual Plan 1970-71 Part 1 Notes - Planning Commission (Planning Commission, 1970)
Agriculture has been the main stay of the economy of this Union territory inasmuch as 44% of the working force was employed in it in 1961. Apart from satisfying the basic need of food to the growing population, it also creates bulk of wage goods to the non-agricultural sector and industry in the Territory. the record of progress under the sector holds out great promise for the future. The green revolution ushered in by the Administration involves a judicious combination of modern technology and traditional practices. the farmer responded readily to a combination of good prices, high-yielding seeds and adequate fertilisers. He look to improved farm practices as he did to non-traditional farm inputs and adapted himself to the new strategy of agricultural development with considerable enthusiasm.
Government of the Union Territory of Pondicherry